2016
DOI: 10.5194/bg-2016-362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-distance electron transport occurs globally in marine sediments

Abstract: <p><strong>Abstract.</strong> Recently, long filamentous bacteria have been reported to conduct electrons over centimetre distances in marine sediments. These so-called cable bacteria perform a novel "electrogenic" form of sulfur oxidation, whereby long-distance electron transport links sulfide oxidation in deeper sediment horizons to oxygen reduction in the upper millimetres of the sediment. Electrogenic sulfur oxidation exerts a strong impact on the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…As the relative rates of DNRA and denitrification are of global interest as global N loads increase (Gruber and Galloway ; Conley et al ; Steffen et al ), understanding the conditions under which DNRA may be enhanced (or denitrification suppressed) is critical. If cable bacteria are significantly enhancing DNRA, then the stable, seasonally hypoxic systems most closely associated with cable bacteria (Malkin et al ; Seitaj et al ; Burdorf et al , ; Nielsen ) may become more N‐recycling during the seasonal cable bacteria dominance. This is particularly interesting as the Fe‐cycling associated with cable bacteria has been shown to buffer against euxinia (Seitaj et al ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As the relative rates of DNRA and denitrification are of global interest as global N loads increase (Gruber and Galloway ; Conley et al ; Steffen et al ), understanding the conditions under which DNRA may be enhanced (or denitrification suppressed) is critical. If cable bacteria are significantly enhancing DNRA, then the stable, seasonally hypoxic systems most closely associated with cable bacteria (Malkin et al ; Seitaj et al ; Burdorf et al , ; Nielsen ) may become more N‐recycling during the seasonal cable bacteria dominance. This is particularly interesting as the Fe‐cycling associated with cable bacteria has been shown to buffer against euxinia (Seitaj et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This site is usually located in the salt wedge of the estuary, and is characterized by periodical hypoxia in the bottom waters during low rainfall, combined with aphotic sediments due to the high turbidity of the overlying freshwater layer (Roberts et al ). The site has been used previously for studies of the fate of nitrate during nitrate reduction (Roberts et al , ) and investigation of the sediment has shown an in situ population of cable bacteria (Burdorf et al ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cable bacteria belong to the family Desulfobulbaceae of the Deltaproteobacteria and are currently represented by two candidate Genera , Candidatus Electronema and Candidatus Electrothrix (Trojan et al ., ). The cable bacteria are widespread in shallow marine sediments (Risgaard‐Petersen et al ., ; Malkin et al ., ; Burdorf et al ., ). In situ mass developments of cable bacteria have been documented in a seasonally hypoxic marine basin in the Netherlands (Grevelingen) (Seitaj et al ., ).…”
Section: Sulfur Oxidationmentioning
confidence: 97%